Lectures in Modern Methods of Teaching English Language and Literature for MA students majoring in 035 Philology (English language and literature) - Huszti Ilona; Fábián Márta; Nagy-Kolozsvári Enikő; Густі Ілона; Фабіян Марта; Надь-Коложварі Еніке (Ferenc Rákóczi II Transcarpathian Hungarian College of Higher Education, 2020)
Abstract. This booklet contains the notes of five lectures of the discipline for first year master students “Modern methods of teaching English language and literature” as planned in the course syllabus at the Ferenc Rákóczi II Transcarpathian Hungarian College of Higher Education.
https://kmf.uz.ua/wp-content/uploads/2023/05/huszti_fabian_nagy-kolozsvari_lectures_in_modern_methods_2020-1.pdf
Keywords: Modern Methods; Teaching English; MA students